Long‐term changes in macroinvertebrate communities across high‐latitude streams - Milner, Alexander M. (2023)
ABSTRACT: Long-term records of benthic macroinvertebrates in high-latitude streams are essential for understanding climatic changes, including extreme events (e.g. floods). Data extending over multiple decades are typically scarce. Here, we investigated macroinvertebrate community structural change (including alpha and beta diversity and gain and loss of species) over 22 years (1994–2016) in 10 stream systems across Denali National Park (Alaska, USA) in relation to climatological and meteorological drivers (e.g. air temperature, snowpack depth, precipitation). We hypothesised that increases in air temperature and reduced snowpack depth, due to climatic change, would reduce beta and gamma diversity but increase alpha diversity. Findings showed temporal trends in alpha diversity were variable across streams, with oscillating patterns in many snowmelt- and rainfall runoff-fed streams linked to climatic variation (temperature and precipitation), but increased over time in several streams supported by a mixture of water sources, including more stable groundwater-fed streams. Beta-diversity over the time series was highly variable, yet marked transitions were observed in response to extreme snowpack accumulation (1999–2000), where species loss drove turnover. Gamma diversity did not significantly increase or decrease over time. Investigating trends in individual taxa, several taxa were lost and gained during a relative constrained time period (2000–2006), likely in response to climatic variability and significant shifts in instream environmental conditions. Findings demonstrate the importance of long-term biological studies in stream ecosystems and highlight the vulnerability of high-latitude streams to climate change.